Eating Habits and Risk Factors for Diabetes Mellitus in Adulthood in Kotamobagu City - Meildy Esthevanus Pascoal; Ana Barnetje Montol; Kevin Giovani Pascoal; Ingland J. Kamasih (Global Medical & Health Communication (GMHC), 2026)
Diabetes mellitus is a serious global public health problem and is increasingly common in developing countries like Indonesia. Dietary habits and risk factors are considered predictors of type 2 diabetes mellitus (T2DM). This study aims to analyze dietary habits and risk factors in adults with T2DM. This study used a descriptive design. A cross-sectional survey of an adult population aged 30–65 years in the working area of the Gogagoman Community Health Center in Kotamobagu City was conducted in April–June 2025. A nonprobability sampling technique was used to select respondents sequentially until 100 met the inclusion criteria. The analysis included univariate analyses, a bivariate Spearman test, and a multivariate multiple linear regression. The research instrument used a semi-quantitative food frequency questionnaire and the Finnish Diabetes Risk Score (FINDRISC). The data from 100 respondents were normally distributed, with a Kolmogorov-Smirnov p-value of 0.102 (p>0.05). The Spearman test showed that age, BMI, waist circumference, physical activity, fruit and vegetable consumption, history of high blood pressure medication use, family history of diabetes mellitus, and eating habits were statistically significant (p<0.05). In contrast, gender was not significant (p>0.05). Meanwhile, the results of a multiple linear regression analysis showed a correlation coefficient (R) of 0.868 and an R2 of 0.754, indicating that 75.4% of the risk variables for T2DM were associated with the occurrence of diabetes mellitus. The FINDRISC score showed that 19% had low risk, 61% had moderate risk, and 20% had high risk. In conclusion, lifestyle behavior plays an important role in the prevention and management of T2DM. Consuming balanced nutrition by improving diet quality is the primary determinant, with unhealthy eating patterns associated with an increased risk of T2DM.